The Gait of Aqidah Philosophy Study Program Alumni and Their Contributions in the Development of Civil Society - Al Rasyid, Harun; Kamaluddin, Kamaluddin (Al-Fikru: Jurnal Ilmiah, 2024)
This study aims to analyze the work of alumni of the Aqidah and Islamic Philosophy study program, Faculty of Ushuluddin and Islamic Studies, Islamic University of Sumatera Utara, with a focus on observing the contributions made and the strategic areas of civil society development that alumni do. The research used a descriptive study-based qualitative method, and data collection techniques using observation, interviews and document analysis. Furthermore, the data collected was analyzed using the Miles and Hubberman interactive model including data reduction, data presentation, and conclusion drawing. The results of this study indicate three findings, namely first, the role of alumni in taking part in building and fostering communities in Sumatra and several regions in Indonesia has been proven by the community as evidenced by the strategic position of alumni both in government and private institutions. Second, the role of alumni is more focused on the fields of education, counseling and guidance. Third, there is close involvement between study program managers, alumni, and partners in improving the work of alumni. This collaboration has proven to be an important factor in the success of a more sustainable and effective community development program.